Influence of cement content on constitutive model parameters of reinforced completely decomposed granite soil - MA Deshan; ZHANG Dong; TANG Rui; LIU Fei; JIAO Jingzhi; LIU Shaowen; SU Dong (Shenzhen Daxue xuebao. Ligong ban)
Completely decomposed granite (CDG) is widely distributed throughout the South China. Due to its tendency to soften and disintegrate upon contact with water, the post-grouting method is employed in some engineering projects to reinforce the soil around pile foundations in CDG strata. The amount of cement used in the grouting significantly affects the bearing capacity of these foundations. To investigate the impact of varying cement content in grouting on the mechanical properties of reinforced CDG, a series of shear tests were conducted on remolded CDG soil treated with cement contents of 2% ~ 16%. By incorporating numerical simulation, this study calibrated the parameters of the constitutive model for the reinforced CDG under varying cement contents. Through this approach, the relationship among cement content and the parameters of critical state, elasticity, and plasticity of the CDG was identified. It was disclosed that, among the 22 parameters in total, 11 parameters vary with the cement content, while the other 11 parameters remain constant. The variable parameters exhibit either linear or quadratic relationships with the cement content. This study proposes a novel approach to determine the parameters of the constitutive model for the reinforced CDG and provides essential insights into the impact of uneven grouting on the bearing capacity of pile foundations in CDG strata.